1991
DOI: 10.1002/j.1460-2075.1991.tb08059.x
|View full text |Cite
|
Sign up to set email alerts
|

Human GATA-3: a lineage-restricted transcription factor that regulates the expression of the T cell receptor alpha gene.

Abstract: In addition to its role in the recognition of foreign antigens, the T cell receptor (TCR) alpha gene serves as a model system for studies of developmentally‐regulated, lineage‐specific gene expression in T cells. TCR alpha gene expression is restricted to cells of the TCR alpha/beta+ lineage, and is controlled by a T cell‐specific transcriptional enhancer located 4.5 kb 3′ to the C alpha gene segment. The TCR alpha enhancer contains four nuclear protein binding sites called T alpha 1‐T alpha 4. In this report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
231
1
5

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(242 citation statements)
references
References 37 publications
5
231
1
5
Order By: Relevance
“…Footprint El encompasses potential binding sites for Ets and Gata family transcription factors. Several Ets family members (Ets-1, Ets-2, and Elf-1) (1, 58) and a Gata family member (Gata-3) are expressed at high levels in T cells (24,27,32). In Jurkat extracts, the region around these two sequences is well protected and includes the presence of a hypersensitive site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Footprint El encompasses potential binding sites for Ets and Gata family transcription factors. Several Ets family members (Ets-1, Ets-2, and Elf-1) (1, 58) and a Gata family member (Gata-3) are expressed at high levels in T cells (24,27,32). In Jurkat extracts, the region around these two sequences is well protected and includes the presence of a hypersensitive site.…”
Section: Resultsmentioning
confidence: 99%
“…4A). The choices for nucleotide substitutions were based on previous studies in which either factor binding or functional activity of the particular binding site was destroyed (3,23,24,38). These mutant enhancer fragments were subcloned into the luciferase expression vector with the minimal CD4 promoter and transiently transfected into D10 T cells, and the enhancer activity was then compared with activities unmutated enhancer constructs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, during development of DP to CD4 SP cells the expression levels of the TCR and GATA3 will increase. It may be possible that GATA3 directly regulates TCRa and b transcription, as binding sites have been identified in these loci [3,36]. As GATA3 expression is not induced in the CD8 cell lineage [5,7], it is clear that different nuclear factors should be responsible for the regulation of the expression levels of CD5 and TCR molecules in the CD8 lineage.…”
Section: Discussionmentioning
confidence: 99%
“…One of the transcription factors indispensable for CD4 lineage development is the zinc-finger transcriptional regulator GATA3, which was originally identified as a protein that binds to the TCRa gene enhancer [3]. GATA3 is indispensable for early T cell lineage development and also plays a crucial role in the differentiation of mature Th2 effector cells by regulating transcription and chromatin configuration of the IL-4, IL-5 and IL-13 Th2 cytokine genes (reviewed in [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Random site selection has suggested that additional nonconsensus sequences can bind GATA proteins with high affinity (32,42). Two of the GATA transcription factors (GATA-1 and GATA-3) are expressed in a tissuerestricted fashion and have been shown previously to regulate lineage-specific gene expression in erythroid cells and T lymphocytes, respectively (24,29,33,72,78). Moreover, homozygous disruption of the GATA-1 gene in mice results in a specific block in erythroid development (56,68).…”
mentioning
confidence: 99%